Lipoid proteinosis with oral manifestation in a geriatric patient: A unique case report - Jayachandran Sadaksharam; Bakyalakshmi Karthikeyan; Sureshkumar Mahalingam; Sarala Kessavalou (Journal of Indian Academy of Oral Medicine and Radiology, 2015)
Lipoid proteinosis is a very rare, autosomal recessive disorder, characterized by hoarseness of voice, skin scarring, beaded papules along the eyelid margins, and an inability to protrude the enlarged tongue. Infiltration of hyaline material to various organs is found to be responsible for the various manifestations of this disorder. It is mainly prevalent in early infancy and childhood, and is rare in older adults. In this article, we report a 61-year-old patient with the skin and orofacial features of lipoid proteinosis, which is very rarely recorded in literature as far as age and oral manifestation are concerned.